FAMILY PSYCHOLOGY IN FORMING MORAL AND MORAL IMMUNITY AGAINST INFORMATION ATTACK. GENDER STEREOTYPES: THE INFLUENCE OF CHILDREN'S UPbringing and SOCIAL CONSCIOUSNESS (Universal International Scientific Journal, 2026)
This article analyzes the role of family psychology in the formation of moral and spiritual immunity in a person in the conditions of information attacks. It also scientifically illuminates the impact of gender stereotypes on the process of raising children and the formation of social consciousness in society. The study examines the impact of the psychological environment in the family, parental upbringing and gender views on the worldview of the younger generation, and substantiates that strengthening moral and spiritual values ​​is an important factor in ensuring information security.
Keywords: family psychology; information attacks; moral and ethical immunity